(untitled) (South East Asia Journal of Public Health, 2013)
The increase in life expectancy, from under 40 years in all areas of the world two centuries ago to over 80 years to-day in many developed countries, has fundamentally improved the human condition. Though life expectancy is a well known measure for longevity of a population, period life expectancy is affected by age-specific mortality in-tensely. Early aged mortality creates disparity in life expectancies, which is very common for many under developed and developing countries. Adequate link exists between changes in age-specific mortality and lifespan inequality, and key to this relationship is a youngold threshold age, below and above which mortality decline respectively de-creases and increases lifespan inequality. Besides socio-economic importance, this thresholds location modifies the correlation between changes in life expectancy and lifespan inequality. Zhang-Vaupels theorem of estimating threshold age is applied to estimate the threshold age for a developing country Bangladesh, using the data of Matlab Health and Demographic Surveillance System. The graphical estimate of threshold age was found to be 70 to 72 years for male and 72 to 75 years for female of Matlab HDSS-2010. These findings imply the imminent longevity for the population of Matlab HDSS. DOI: http://dx.doi.org/10.3329/seajph.v2i2.15947 South East Asia J Public Health | Jul-Dec 2012 | Vol 2 Issue 2 | 48-54